A 2D model for low-pressure hollow cathode arc discharges in argon. (20th November 2018) - Cong, Shiyuan; Wu, Runhui; Mu, Lei; Sun, Jizhong; Wang, Dezhen
Abstract: A 2D fluid model is presented in this paper to study axisymmetric hollow cathode arc discharge, in which the equations of particle and particle energy transport, neutral gas flow and heating, and cathode thermal balance are included. This model can overcome the deficiency of other non-self-consistent models, where some boundary conditions must be predefined. In this work, the spatial variations of the electron density and temperature, gas temperature, and cathode wall temperature were investigated under various radii, thicknesses and surface emissivities of the hollow cathode. It is found that the cathode wall temperature was far below the measured wall temperature if the model neglected the contribution of the Joule heating of ions, while the calculated value was in good agreement with the measured one if the model took into account the contribution of the Joule heating of ions. This finding indicates that the Joule heating of ions played an important role and should not be neglected in the modeling of low-pressure hollow cathode discharges. The results also show that the domain and location of the plasma column inside the cathode tube were dependent on the pressure, pressure gradient, and gas temperature, and that the surface thermal radiation was a primary heat loss mechanism on the cathode. In addition, this paper also analyzed the formation of the cathode sheath and evaluated the sheath thickness.